Sauna kogemustest Eestis, Balti riikides ja Põhjamaades - Raudjärv, Matti (Estonian Discussions on Economic Policy, 2024)
The article gives a brief overview of the history of sauna use and the personal saunas of the undersigned and development of sauna use: examples are brought from sauna use in Nordic and Baltic countries and international sauna use practices. The author’s saunas and personal sauna experience in Estonia and outside Estonia is separately described. A brief overview of the construction of own smoke sauna and its use is given. As 2023 is the Year of Sauna in Estonia, the main events of the year are listed, incl. the essence of the Estonian sauna map. Estonian saunas, whisking and the art of making sauna whisks are described and recommendations are provided for the selection of stones for the sauna heater. Hints about information on old sauna customs and traditions are given to the reader. The Estonian smoke sauna tradition has been included in the UNESCO List of Cultural Heritage of the Humanity since 2014. The article dwells on the ISA (International Sauna Association) membership (Estonia is a member as well). A new type of Estonia sauna is described – the sumesauna. Annexes contain information about the Estonian sauna capital Kadrina and the respective developments. A brief overview is given starting from the historical Estonian sauna architecture until today (incl. the modern and industrially produced saunas). A statement about regular sauna use and good health. Examples of modern saunas in Helsinki, Finland, and Sweden are provided. For conclusion, the text of the Declaration of Sauna Peace is presented. A long list of literature used and recommended is included. The article has been illustrated with 30 colour photos. The full text of the paper has been published in Estonian as different aspects of sauna are mainly familiar to Estonia and the Baltic and Nordic countries (although many countries know their own “traditional sauna”). For instance, in English and German the sauna culture should already be described/explained in a thick book to enable people from other nationalities to understand and experience all these different aspects. The literature sources used in the full paper are mainly in Estonian and useful for those who would like to have even more thorough information but those who cannot read Estonian would probably not translate them into their native language